Outcomes following Purely Endoscopic Endonasal Resection of Pituitary adenomas (Journal of Enam Medical College, 2013)
Background: The use of endoscope for the management of pituitary adenoma is not new. The better magnification and illumination provided by the endoscope gives better outcome than microscopic pituitary surgery. Objective: To find out the benefits of endoscope in relation to microscopic surgery. Materials and Methods: We performed 45 cases of pituitary adenoma surgery by endoscopic endonasal approach from July 2008 to July 2010. Results: Forty five cases underwent endoscopic transsphenoidal approach. Gross total removal was done in 35 cases and subtotal removal was done in 10 cases. Residual tumours were seen in 10 cases (22%) in postoperative follow-up MRI scan. Visual improvement was satisfactory, and hormonal improvement of functional adenoma was nice. Postoperative visual acuity and visual field were improved in 75% cases. There were 37% cases of temporary diabetes insipidus and about 4.5% cases of permanent diabetes insipidus. The average duration of follow-up was 20 months. One patient required reexploration to correct visual deterioration in the immediate postoperative period. There were 4.5% cases of CSF leak and 6.6% mortality. Mortality was due to electrolyte imbalance and improper management of infection and hydrocephalus. Conclusion: Endoscopic endonasal pituitary surgery now has become a gold standard surgery for most of the pituitary adenomas because of its better advantages in relation to microscopic surgery and less complications and less hospital stay. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13869 J Enam Med Col 2013; 3(1): 18-23